The Role of Green Supply Chain Management Practices on Environmental Performance of Firms: An Exploratory Survey in Brazil - Teixeira, Adriano Alves [UNESP]; Moraes, Tiago E. C. [UNESP]; Teixeira, Talita Borges [UNESP]; Battistelle, Rosane A. G. [UNESP]; Araújo, Elton Gean; de Seabra, Quintino Augusto Có [UNESP] (MDPI, 2023)
Our work is one of the rare studies that sought to verify the relationship between green supply chain management practices and environmental performance in companies in an emerging Latin American market. We surveyed in the specialized literature on environmental management and green supply chain management (GSCM) for practices were most cited and can influence this relationship. From this review, an e-survey was constructed and answered by 79 environmental or supply chain/logistics managers from the surveyed sample. The results indicate that there is a positive and significant relationship between the adoption of green supply chain management practices and the environmental performance of the companies. We found that GSCM practices: environmental management with total quality (GSCM4), cooperation with suppliers to achieve environmental management objectives (GSCM7), and cross-functional cooperation for environmental improvements (GSCM3), in this order. These are the main GSCM practices that influence the environmental performance in the surveyed companies. Thus, our study adds relevant information to the specialized literature and for the decision-making of managers, professionals, and government working in this area of study.